Barreras de acceso y calidad en el control prenatal (2023)
Introduction: Prenatal care (PC) is a cost-effective strategy that prevents maternal and perinatal mortality and morbidity. Although PC in Colombian pregnant women shows an enrollment rate of 94%, this condition does not impact the decline of maternal perinatal mortality. Objective: To describe the obstacles to access to PC and the perceived quality of care for pregnant women in Meta. Materials and methods: A cross-sectional, observational and descriptive study was designed and a survey was applied to inquire about aspects such as perception of quality of care, obstacles to access and comprehensiveness of care. Results: 306 pregnant women were included in the study, whose average age was 24 years. 66% had one or two pregnancies, 15% had abortions and 25% had a cesarean section. 74.17% of them had four or more prenatal controls. Risk factors were associated with attending less than four controls, while perception of quality had an odds ratio (OR) of 22.7; additionally, beginning PC during the second trimester had an OR of 5.64, low income level an OR of 5.12, and low maternal schooling an OR of 3.62. Conclusion: Improving the quality and integrity of PC by health providers is a complementary strategy to ensure its effect on the reduction of maternal and perinatal morbidity and mortality. © 2017, Universidad Nacional de Colombia. All rights reserved.